St. Lucia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2002)
This Selected Issues paper on St. Lucia examines challenges facing the Windward Islands banana industry with a focus on the socioeconomic impact and production recovery strategies. The paper focuses on St. Luciathe-region's largest producer and most populous island. It reviews recent developments in the tourist industry in St. Lucia and its growth potential over the medium term, in an increasingly competitive global tourism market. An overview of developments in the tourist industry in St. Lucia during the 1990s is also presented.